Cryptosporidium and Giardia taxa in faecal samples from animals in catchments supplying the city of Melbourne with drinking water (2011 to 2015). Issue 1 (December 2016) - Koehler, Anson; Haydon, Shane; Jex, Aaron; Gasser, Robin
Abstract Background In a long-term program to monitor pathogens in water catchments serving the City of Melbourne in the State of Victoria in Australia, we detected and genetically characterisedCryptosporidium andGiardia in faecal samples from various animals in nine water reservoir areas over a period of 4 years (July 2011 to November 2015). Methods This work was conducted using PCR-based single-strand conformation polymorphism (SSCP) and phylogenetic analyses of portions of the small subunit of ribosomal RNA (SSU ) and 60 kDa glycoprotein (gp60 ) genes forCryptosporidium, and triose-phosphate isomerase (tpi ) gene forGiardia . Results The prevalence ofCryptosporidium was 1.62 % (69 of 4, 256 samples); 25 distinct sequence types were defined for pSSU, and six forgp60 which representedC. hominis (genotype Ib - subgenotype IbA10G2), C. cuniculus (genotype Vb - subgenotypes VbA26, and VbA25), andC. canis, C. fayeri, C. macropodum, C. parvum, C. ryanae, Cryptosporidium sp. "duck" genotype, C. suis andC. ubiquitum as well as 12 novelSSU sequence types. The prevalence ofGiardia was 0.31 % (13 of 4, 256 samples); all three distincttpi sequence types defined represented assemblage A ofG. duodenalis . Conclusions Of the 34 sequence types (genotypes) characterized here, five and one have been recorded previously forCryptosporidium andGiardia, respectively, from humans. Novel genotypes ofCryptosporidium andGiardia were recorded forSSU (n = 12), gp60 (n = 4) andtpi (n = 1); the zoonotic potential of these novel genotypes is presently unknown. Future work will continue to monitor the prevalence ofCryptosporidium andGiardia genotypes in animals in these catchments, and expand investigations to humans. Nucleotide sequences reported in this paper are available in the GenBank database under accession nos. KU531647–KU531718.